Predicting cervical cancer screening participation using self-care behaviors among women in Iran - Marzieh Ghasemi; Mitra Savabi-Esfahani; Mahnaz Noroozi; Mohammad Sattari (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Cervical cancer screening is an effective and accessible method for preventing this cancer. However, low participation rates among women have been reported. Self-care is one of the solutions to improve access to health services. This study was conducted to determine the prediction of cervical cancer screening participation using self-care behaviors among women in Iran. MATERIALS AND METHODS: This cross-sectional study was conducted on 310 eligible women who were referred to comprehensive health centers and women's clinics in teaching hospitals in Isfahan, Iran, from November 2020 to April 2021. Participants were enrolled using convenience sampling. The data collection tool included researcher-made questionnaires on personal and fertility characteristics, participation in cervical cancer screening, and self-care behaviors related to cervical cancer and its screening. Descriptive and inferential statistical methods were used for data analysis using the Statistical Package for the Social Sciences (SPSS) version 22 software. RESULTS: The results showed that the intention to undergo screening was low among individuals who had not undergone screening. Lack of awareness and not having enough time were the most common barriers to screening. The results of logistic regression analysis indicated that self-efficacy was the significant predictor of cervical cancer screening. With an increase in the self-care score, the 12% chance of doing a Pap smear increases significantly (P = 0.002). Furthermore, the results of multiple regression showed that with an increase in the self-care score, the chance of women who refer to screening every year, every 2-3 years, and every 4-5 years is increased to 25% (P = 0.001), 34% (P < 0.001), and 11% (P = 0.032), respectively, compared with non-referral. DISCUSSION: According to the results, self-care was a predictor of performing a Pap smear, and it was related to its regular performance of Pap smear too. Therefore, designing and implementing necessary interventions to increase self-care behaviors can improve women's participation in cervical cancer screening and its regularity.